Generative Grammar: A Meaning First Approach - Sauerland, Uli; Alexiadou, Artemis (Frontiers in Psychology, 2020)
The theory of language must predict the possible meaning-signal (i.e. sound and sign) pairings of a language. We argue for a Meaning First architecture of language where a thought structure is generated first. The thought structure is then realized using language to communicate the thought, to memorize it, or perhaps with another purpose. Our view contrasts with the T-model architecture of mainstream generative grammar, according to which distinct phrase-structural representations – Phonetic Form (PF) for articulation, Logical Form (LF) for interpretation – are generated within the grammar. At the same time, our view differs from early transformational grammar and generative semantics: We view the relationship between the thought structure and the corresponding signal as one of effective compression. The Meaning First architecture allows a greater degree of independence between thought structures and the linguistic signal. We present three arguments favoring this type of independence. First we argue that scopal properties can be better explained if we only compare thought structures independent of the their realization as a sentence. Secondly, we argue that Meaning First architecture allows contentful late insertion, an idea that has been argued for in Distributed Morphology already, but as we argue is also motivated by the division of the logical and socio-emotive meaning content of language. Finally, we show that only the Meaning First architecture provides a satisfying account of the mixing of multiple languages by multilingual speakers, especially for cases of simultaneous articulation across two modalities in bimodal speakers. Our view of the structure of grammar leads to a reassessment of priorities in linguistic analyses: while current mainstream work is often focused on establishing one-to-one relationships between concepts and morphemes, in our view the focus should be only on the overall simplicity of the conceptual calculus and the realization procedure